First‐trimester risk assessment based on ultrasound and cell‐free DNA vs combined screening: a randomized controlled trial. (4th March 2018) - Kagan, K. O.; Sroka, F.; Sonek, J.; Abele, H.; Lüthgens, K.; Schmid, M.; Wagner, P.; Brucker, S.; Wallwiener, D.; Hoopmann, M.
ABSTRACT: Objective: This was a randomized controlled trial to compare risk assessment by first‐trimester combined screening (FTCS) with an approach that combines a detailed ultrasound examination at 11–13 weeks' gestation and cell‐free DNA (cfDNA) analysis. Methods: Pregnant women with a normal first‐trimester ultrasound examination at 11–13 weeks' gestation (fetal nuchal translucency (NT) ≤ 3.5 mm and no fetal defects) were randomized into one of two groups. In the first group, risk of aneuploidy was assessed using FTCS based on the most recent UK Fetal Medicine Foundation algorithm. In the second group, risk assessment was based on ultrasound findings and cfDNA analysis. An additional tube of blood was collected for FTCS in case the cfDNA analysis was uninformative. Primary outcome was false‐positive rate in screening for trisomy 21. A case was considered false positive if the karyotype was not trisomy 21 and if the risk for trisomy 21 was >1:100, irrespective of the method of risk calculation. Results were compared using 95% CIs using the Clopper–Pearson method. Results: Between October 2015 and December 2016, 1518 women with singleton pregnancy underwent first‐trimester screening. Thirty‐one (2.0%) pregnancies were not eligible for randomization due to increased NT (> 3.5 mm) and/or fetal defect. After exclusion of women who declined randomization ( n  = 87) and cases of fetal death and loss to follow‐up ( n  = 24), 688 pregnancies were randomized into the FTCS arm and 688 into the ultrasound + cfDNA analysis arm. There were no differences in maternal and gestational age, maternal weight and BMI, ethnicity, use of assisted reproduction and cigarette smoking between the two arms. In the ultrasound + cfDNA analysis arm, median risk for trisomy 21 was 1 in 10 000. None of the cases had a risk above 1: 100 (95% CI, 0.0–0.5%). In the FTCS arm, the median risk for trisomy 21 was 1 in 3787 and in 17 cases, the risk was higher than 1:100, which corresponds to 2.5% (95% CI, 1.5–3.9%) of the FTCS study‐arm population. Conclusion: Our study has shown that first‐trimester risk assessment for trisomy 21 that includes a detailed ultrasound examination as well as NT measurement and is followed by cfDNA testing is associated with a significant reduction in the false‐positive rate compared with FTCS. This approach obviates the need for maternal serum free β‐human chorionic gonadotropin and pregnancy‐associated plasma protein‐A in screening for fetal aneuploidy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2018; 51: 436–436